Difusion of tritium, generated in lithium methanetitanate LI2TIO3 in process of warm neutron radiation in WWRK reactor - Kuykabayeva, A. A.; Bekman, I. N.; Buntseva, I. M.; Tazhibayeva, I. L. (Recent Contributions to Physics, 2013)
Automation and processing software was developed for interpretation of the results of reactor experiments on tritium release study. Tritium was continuously generated as a result of nuclear reaction of lithium-6 and thermal neutrons under variable thermal impacts on lithium metatitanate. Main gas release parameters, which are necessary for assessment of applicability to use the lithium titanate granules in tritium blankets, were calculated: tritium retention/release ratio, retention time, activation energy of HT thermodesorption, activation energy of T+ bulk diffusion, and corresponding pre-exponential (frequency) factors. It was shown that tritium diffusion coefficient was actively increasing during first 10 months of reactor irradiation of lithium metatitanate, then effective diffusion coefficient stabilized at the value of 1.3×10-7 cm2 /s and afterwards the coefficient didn’t change or changed insignificantly.